2010
DOI: 10.1186/cc8909
|View full text |Cite
|
Sign up to set email alerts
|

Infections of respiratory or abdominal origin in ICU patients: what are the differences?

Abstract: IntroductionThere are few data related to the effects of different sources of infection on outcome. We used the Sepsis Occurrence in Acutely ill Patients (SOAP) database to investigate differences in the impact of respiratory tract and abdominal sites of infection on organ failure and survival.MethodsThe SOAP study was a cohort, multicenter, observational study which included data from all adult patients admitted to one of 198 participating intensive care units (ICUs) from 24 European countries during the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 37 publications
(62 reference statements)
6
45
1
2
Order By: Relevance
“…In an analysis of patients from the Sepsis Occurrence in Acutely Ill Patients (SOAP) study, Volakli et al reported no differences in mortality rates among patients with abdominal infections and those with respiratory infections [6]. The higher mortality rate in patients with abdominal infections in our study may be explained by a number of differences between abdominal and other infections.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In an analysis of patients from the Sepsis Occurrence in Acutely Ill Patients (SOAP) study, Volakli et al reported no differences in mortality rates among patients with abdominal infections and those with respiratory infections [6]. The higher mortality rate in patients with abdominal infections in our study may be explained by a number of differences between abdominal and other infections.…”
Section: Discussioncontrasting
confidence: 48%
“…Abdominal infections are more often associated with septic shock and acute kidney injury than are infections in other sites [5, 6]. The spectrum of disease and severity is broad and management of these infections is challenging [79].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between BMI and development of AKI has been demonstrated in prior large cohort studies (11, 48, 49, 50) although only one of these studies evaluated septic patients with AKI (11). We also found that patients with an abdominal source of infection were more likely to develop AKI than patients with a pulmonary source, which confirms prior data (11, 51). …”
Section: Discussionsupporting
confidence: 91%
“…It has previously been suggested that abdominal infections may be more severe (30, 31) than respiratory infections. A recent study showed no differences in age, sex, severity score, or mortality rates between the two groups, but the development of septic shock, early coagulation, and acute renal failure was more common in patients with abdominal infections (32). The fact that abdominal infections dominate should, if anything, influence our mortality rates negatively.…”
Section: Discussionmentioning
confidence: 96%